Developing Speaking Skill Through Storytelling (A Case Study at Six Grade of MI Nurul Huda Pondok Jaya) (PANOPTICON: Journal of English Studies, 2025)
This study is aimed to know the topic of storytelling for developing speaking skill , to analyze the activities that the teachers used for teaching speaking through the Storytelling , and to find out the student’s response of teaching speaking using Storytelling. This study applies qualitative research method as the analysis presented in the form of text. The data were collected through observation and interview. The result of this study shows that teaching speaking through storytelling makes the students more active and felt confident in speaking with their friends and the teacher using their own words because they enjoyed the learning process.